HMLR analysis on the predictions of work-force management best practices on corporate performance measures: A case study of a millennial workforce in a large-scale it company - Basu, Shouvonik; Mohanty, Jitendra; Singh, Saranjit (Journal of Asian Scientific Research, 2025)
The objective of the present article is to investigate the impact of Workforce Management (WFM) best practices on the overall effectiveness of Corporate Performance Measures (CPM) using a case study of a large-scale IT company employing predominantly a millennial workforce. This analysis effectively establishes the correlation between these two variables by presenting substantiated evidence regarding the impact of these practices on overall corporate performance. The facets of WFM were grouped into Business Planning and Control; Talent Acquisition and Competency; and Employee Performance and Attitude, whereas CPM facets were classified into Organizational Culture and Efficiency; and Employee Satisfaction and Motivation. A closed-ended questionnaire survey with 115 questions was designed to investigate the complex interaction between the above variables. Statistical analyses, including bivariate, normality tests (skewness and kurtosis), correlation, and Hierarchical Multiple Linear Regression (HMLR) analyses, were conducted to examine the relationships and test the hypotheses. The findings reveal that bundles focused on business planning and talent acquisition were significant predictors of organizational culture and efficiency. In contrast, talent acquisition and employee performance were found to be strong determinants of satisfaction and motivation. The research provides empirical evidence that strategic WFM implementation positively affects overall corporate outcomes by fostering a collaborative and innovative work environment. These results also offer practical guidance for HR professionals seeking to design workforce strategies that align with the expectations of millennial, digitally savvy employees.